Clinical efficacy of amrubicin in patients with small cell lung cancer relapse after first‐line treatment including immune checkpoint inhibitors: A retrospective multicenter study (TOPGAN 2021‐01). Issue 2 (21st November 2022) - Uematsu, Shinya; Kitazono, Satoru; Tanaka, Hisashi; Saito, Ryota; Kawashima, Yosuke; Ohyanagi, Fumiyoshi; Tozuka, Takehiro; Ryosuke, Tsugitomi; Sakatani, Toshio; Horiike, Atsushi; Yoshizawa, Takahiro; Saiki, Masafumi; et al.
Abstract: Background: The therapeutic efficacy of cytotoxic anticancer drugs has been reported to be enhanced after immune checkpoint inhibitors (ICI) in non–small cell lung cancer; however, it is unclear whether the same is applicable for small cell lung cancer (SCLC). We evaluated the efficacy of second‐line amrubicin (AMR) following first‐line platinum‐based chemotherapy and ICI combination therapy (chemo‐ICI) in SCLC. Patients and Methods: We retrospectively enrolled consecutive patients with SCLC treated with AMR as a second‐line following chemo‐ICI as first‐line between July 2019 and April 2021 from 16 institutions throughout Japan. We investigated the therapeutic effectiveness, safety, and efficacy‐enhancing variables of AMR. Results: Overall, 89 patients treated with AMR after first‐line chemo‐ICI were analyzed. The overall response rate (ORR) was 29.2% (95% confidence intervals [CI], 20.1–39.8) and median PFS (m PFS) was 2.99 months (95% CI, 2.27–3.65). Patients who relapsed more than 90 days after receiving first‐line platinum combination therapy (sensitive relapse) exhibited greater ORR (58.3% vs. 24.7%, p  = 0.035) and m PFS (5.03 vs. 2.56 months, p  = 0.019) than patients who relapsed in <90 days (refractory relapse). Grade 3 or higher adverse events were mainly hematological toxicity. Conclusions: Our study suggested that the therapeutic effect of AMR was not enhanced after ICI on SCLC. However, AMR may be effective in cases of sensitive relapse after chemo‐ICI. There was no increase in severe toxicity associated with AMR after ICI. Abstract : Our study suggested that the therapeutic effect of AMR was not enhanced after ICI on SCLC. However, AMR may be effective in cases of sensitive relapse after chemo‐ICI.